Classification and Monitoring of Kahayan River Riparian Zone Settlement Expansion Utilizing Satellite Imagery to Prevent Environmental Damage - Sutrisno, Herwin; Susi, Theresia; Hartanto, Singgih; Perkasa, Petrisly; Supriadi, Benong; Mantana, Handri (Department of Urban and Regional Planning, Diponegoro University, 2025)
As the population residing along the Kahayan River increased, many tall trees were cut down. This rapid growth of settlements negatively impacted environmental quality and accelerated soil erosion. Human activities such as tree logging and mining further aggravated erosion along the riverbanks, increasing the risk of flooding and damaging ecosystems. Settlements on the riverbanks became vulnerable to flooding, especially during heavy rains, which could destroy buildings and cause significant financial losses. This study aims to understand the relationship between settlement development and forest loss in the riparian zone of the Kahayan River in Palangka Raya City. To achieve this goal, high-resolution imagery and Geographic Information System (GIS) were used in conjunction with periodic satellite image classification methods. The main findings of the study show a drastic landscape transformation. During the study period, settlement areas expanded exponentially by 412%, increasing from 47.44 hectares to 243.07 hectares. This trend inversely correlated with a significant 57% reduction in riparian forest cover, decreasing from 390.08 hectares to 166.66 hectares. These findings have dual implications. Institutionally, the data provide an urgent empirical basis for local governments to formulate stricter and more effective spatial planning policies. Theoretically, this study strengthens understanding of the cause-and-effect relationship between urbanization processes and the degradation of sensitive riparian ecosystems. This quantitative evidence underscores the need to integrate urban planning and environmental conservation to achieve sustainable development.